A robust digital image watermarking using repetition codes against common attacks - Hassan, Abdullahi Mohamud (2015)
Digital watermarking is hiding the information inside a digital media to protect for such documents against malicious intentions to change such documents or even claim the rights of such documents. Currently the capability of repetition codes on various attacks in not sufficiently studied. In this project, a robust frequency domain watermarking scheme has been implemented using Discrete Cosine Transform (DCT). The idea of this scheme is to embed an encoded watermark using repetition code (3, 1) inside the cover image pixels based on Discrete Cosine Transform (DCT) embedding technique. The proposed methods have undergone several simulation attacks tests in order to check up and compare their robustness against various attacks, like salt and pepper, speckle, compress, Gaussian, image contrast, resizing and cropping attack. The robustness of the watermarking scheme has been calculated using Peak Signal-To-Noise Ratio (PSNR), Mean Squared Error (MSE) and Normalized Correlations (NC). In our experiments, the results show that the robustness of a watermark with repetition codes is much better than without repetition codes